Răspuns :
a:b = 5⇒a = 5b
c:b = 3⇒c = 3b
a - c = 36
5b - 3b = 36⇒ 2b = 36⇒ b=36:2⇒ b=18
a = 5b = 5×18 ⇒ a=90
c = 3b = 3 ×18 ⇒ c=54
suma celor 3 numere = a + b + c = 90 + 18 + 54 = 162
c:b = 3⇒c = 3b
a - c = 36
5b - 3b = 36⇒ 2b = 36⇒ b=36:2⇒ b=18
a = 5b = 5×18 ⇒ a=90
c = 3b = 3 ×18 ⇒ c=54
suma celor 3 numere = a + b + c = 90 + 18 + 54 = 162
a:b=5 => a=5b
c:b=3 => c=3b
a-b=36
____________
5b-3b=36
2b=36
b=36:2
b=18
a=18×5
a=90
c=18×3
c=54
_______
a+b+c=90+18+54=162
c:b=3 => c=3b
a-b=36
____________
5b-3b=36
2b=36
b=36:2
b=18
a=18×5
a=90
c=18×3
c=54
_______
a+b+c=90+18+54=162